2023
DOI: 10.48550/arxiv.2301.13591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zero3D: Semantic-Driven Multi-Category 3D Shape Generation

Abstract: Semantic-driven 3D shape generation aims to generate 3D objects conditioned on text. Previous works face problems with single-category generation, low-frequency 3D details, and requiring a large number of paired datasets for training. To tackle these challenges, we propose a multi-category conditional diffusion model. Specifically, 1) to alleviate the problem of lack of large-scale paired data, we bridge the text, 2D image and 3D shape based on the pre-trained CLIP model, and 2) to obtain the multi-category 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Diffusion-based approach (Tevet et al 2022b;Zhang et al 2022;Xin et al 2023): diffusion models (Ho and Salimans 2022;Song et al 2020) have recently attracted significant attention and have shown remarkable breakthroughs in various areas such as video (Luo et al 2023), image (Ramesh et al 2022), and 3D point cloud generation (Han, Liu, and Shen 2023), etc. Current motion generation methods based on diffusion models (Tevet et al 2022b;Zhang et al 2022;Xin et al 2023) have achieved exceptional results using different denoising strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-based approach (Tevet et al 2022b;Zhang et al 2022;Xin et al 2023): diffusion models (Ho and Salimans 2022;Song et al 2020) have recently attracted significant attention and have shown remarkable breakthroughs in various areas such as video (Luo et al 2023), image (Ramesh et al 2022), and 3D point cloud generation (Han, Liu, and Shen 2023), etc. Current motion generation methods based on diffusion models (Tevet et al 2022b;Zhang et al 2022;Xin et al 2023) have achieved exceptional results using different denoising strategies.…”
Section: Introductionmentioning
confidence: 99%